THE INFLUENCE OF BRAND AMBASSADORS AND GIFT GIVING ON PURCHASE DECISIONS ON LEMONILO NOODLES AND NCT DREAM - Sari, Aminah Mustika; Pradnyana, I Dewa Putu Rai Wira; Sidi, Agus Purnomo (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
There’s many producers of food and beverage products on the market requires producers to innovate and plan the right marketing strategy in order to compete with similar producers. A strategy that is currently being used by producers is to work with public figures as brand ambassadors. Choosing the right brand ambassador can make the product widely recognised by the public and attractive to buy, resulting in increased sales. Apart from brand ambassadors, another strategy used by producers is to give gifts. Gifts are considered capable of attracting consumers to make purchases. This research aims to determine the effect of Brand Ambassadors on Purchasing Decisions and to determine whether there is an effect of Gift Giving on Purchasing Decisions. This research is quantitative research, the data used is primary data, namely data obtained from distributing questionnaires. The sampling technique in this research used a non-probability method with purposive sampling technique and obtained 40 respondents. The analysis used is multiple linear analysis, where previously validity and reliability tests were carried out. The results showed that the brand ambassador variable had a significant effect on the purchasing decision variable and the gift giving variable was also significant to the purchasing decision variable.